CUSTOMER SUPPORT CHATBOT USING NATURAL LANGUAGE PROCESSING - Richa Ranveera; Akanksha Kesharwani; Srishti Kumari (International Journal of Innovations in Engineering Research and Technology, 2021)
Customer support has become one of the most important communication tools used by companies to provide before and after-sale services to customers. The immediate response to all customer query is very necessary for company success. In this paper we focus on, providing a Chatbot that will see to all the queries user have and will provide a solution or answer to that.Usually companies have many people involved for dealing customer queries but this is time-consuming and tedious job to be done. For solving these problems, Chatbot was created for use. Generally, the frequently asked customer questions and corresponding answers and description about the company details are stored in a text file. So in this model, it will take the customer’s question as input, preprocessing them using some Natural Language Processing techniques that include Tokenization, Lemmatization, and stemming, find the cosine similarity between the user query and provides a score for each answer,the more suitable and perfect answer with more cosine similarity score will be considered as the answer for the given question. The Chatbot helps to provide high accuracy by proving the correct and satisfying answer to the customer's question for a company.